2005
DOI: 10.1111/j.1469-7580.2005.00431.x
|View full text |Cite
|
Sign up to set email alerts
|

Motogenic substrata and chemokinetic growth factors for human skin cells

Abstract: Extracellular matrix remodelling and accurate spatio-temporal coordination of growth factor expression are two factors that are believed to regulate mitoses and cell migration in developing and regenerating tissues. The present quantitative videomicroscopical study examined the influence of some of the principal components of extracellular matrix and several growth factors that are known to be expressed in dermal wounds on three important facets of human skin cell behaviour in culture. Keratinocytes, melanocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 62 publications
1
4
0
Order By: Relevance
“…They have found that surface chemistry can affect integrin binding of the cell to the substrate even when utilising the same coating molecule. Sutherland et al [53] have also analysed proliferative effects in human keratinocytes, melanocytes, fibroblasts and myofibroblasts adherent to fibronectin, laminin, collagen and vitronectin with similar results to our work. [6], where increases in protein and decreases in lipid were observed in proliferating cells, with decreases in RNA and increases in DNA between plateau and exponential phase cells.…”
Section: Fluorescence/absorbance Assayssupporting
confidence: 79%
“…They have found that surface chemistry can affect integrin binding of the cell to the substrate even when utilising the same coating molecule. Sutherland et al [53] have also analysed proliferative effects in human keratinocytes, melanocytes, fibroblasts and myofibroblasts adherent to fibronectin, laminin, collagen and vitronectin with similar results to our work. [6], where increases in protein and decreases in lipid were observed in proliferating cells, with decreases in RNA and increases in DNA between plateau and exponential phase cells.…”
Section: Fluorescence/absorbance Assayssupporting
confidence: 79%
“…Previously, it was demonstrated that FN expression decreased in fibroblastic cells with increasing passages and transformation ( Yamada et al , 1977 ). Increased passage number in human keratinocytes has also been demonstrated to correspond to increased migration rates ( Sutherland et al , 2005 ). We therefore assessed the FN expression and motility rates of human primary keratinocytes with increasing passage number (p2–p3, 11–16 days post isolation.…”
Section: Resultsmentioning
confidence: 99%
“…It should be mentioned that the growth factors and cytokines provide motogenic stimulation for keratinocytes that are adherent to matrix, and thus the nature of the matrix on which they are adhered modulates the motogenic response. Numerous studies have demonstrated that the composition of the underlying extracellular matrix can modify the speed of keratinocyte migration in the presence of growth factors (103,(125)(126)(127)(128)(129)(130)(131). Mechanisms by which this occurs include synergistic activation of kinase cascades that converge upon migration (132), and upregulation of specific integrins that contribute to a motile phenotype by the growth factors (95).…”
Section: Dependence On Extracellular Matrixmentioning
confidence: 99%